Enhanced non-linear viscoelastic properties of TATB-based polymer bonded explosives filled with hybrid graphene/multiwalled carbon nanotubes. Issue 115 (4th November 2015) - Lin, Congmei; He, Guansong; Liu, Jiahui; Huang, Zhong; Pan, Liping; Zhang, Jianhu; Liu, Shijun
Abstract : A remarkable synergetic effect between graphene and multiwalled carbon nanotubes in improving the creep resistance are observed for polymer bonded explosives. Abstract : In this work, hybrid graphene/multiwalled carbon nanotubes (MWCNTs) nanofillers were selected to improve to non-linear viscoelastic properties of 1, 3, 5-triamino-2, 4, 6-trinitrobenzene (TATB)-based polymer bonded explosive (PBX). The morphology, mechanical properties, and creep behaviors of TATB-based formulations were studied. The results were compared with the corresponding composites with individual graphene nano-additives. Scanning electron microscopy observation results indicated graphene particles were fairly well dispersed in the nanocomposite filled with hybrid graphene/MWCNTs, while graphene sheets were prone to aggregation in the PBX filled with individual graphene. Hybrid graphene/MWCNTs modified PBX exhibited higher storage modulus in the whole temperature range. The compressive fracture energy ( W c ) and tensile fracture energy ( W t ) at 20 °C were up to 31.6% and 89.6% higher than that of PBX without nanofillers. The creep responses of the composites were determined by short-time creep tests at various temperatures and stresses. The creep compliance curve for TATB-based PBXs showed a remarkable synergetic effect between graphene and MWCNTs in improving the creep resistance. The better dispersion of graphene nanoparticles and higher interfacial zones, which produced strong interfacial interaction between the graphene and polymer matrix to restrict the mobility of polymer chains, were considered as crucial factors for the improvement in the creep resistance for TATB-based PBXs.